Estado da Arte das pesquisas acadêmicas brasileira sobre Etnomatemática e formação de professores (de 2006 a 2016) - Dall’Agnol, Luzitânia (2019)
In order to address the contribution of Ethnomathematics to Teacher Training, this study reports an investigation of the state-of-the-art of Brazilian research developed from 2006 to 2016. To this end, investigations focusing both on Ethnomathematics and on the training of Mathematics teachers were charted. A few categories emerged from the analysis of these studies, including: Initial Professional Education of Teachers; Ethnomathematics and Continuing Education of Mathematics Teachers (with subcategories Mathematics teacher; Indigenous teacher; Documentaries); and Ethnomathematics and Continuing Education of Teachers who Teach Mathematics. The studies revealed that many teachers include the Ethnomathematics Program in their pedagogical practice as a methodological tool and recognize the importance of contextualizing the teaching of Mathematics in combination with sociocultural knowledge and practices